H1N1 Influenza epidemic in children in Baghdad… a hospital based study. - Al-Musawi, Hayder M.; Ghali, Hasanein H.; Nasir, Nadia A.; Hussein, Wisam A.; Al-Janabi, Muhi K. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: A confirmed case of influenza A (H1N1) virus infection is defined as a person with an influenza-like illness with laboratory confirmed influenza A (H1N1) virus infection by real-time RT-PCR or viral culture. Objectives: To identify demographic and clinical predictors, and outcome of proved cases of H1N1 influenza epidemic in children. Patients and methods: This study was conducted in Children Welfare Teaching Hospital/ Medical City/ Baghdad on 67 hospitalized patients aged 1 month to 18 years with signs and symptoms suggestive of influenza during the period of outbreak of pandemic influenza A (H1N1) from 1st of October 2009 to 1st of January 2010. Demographic aspect, clinical coarse, laboratory investigations, treatment and outcome were reported. For each patient 2 nasal, 2 throat swabs and single blood sample were collected, and sent to Central Health Laboratory. All suspected patients received Oseltamivir for 5 days. The data were analyzed statistically by Chi-square (χ2) test and Fisher’s Exact Test. Results: The median age for the studied patients was 7.7 years with a range of 1 month -18 years. 39 patients out of 67 (58.2%) were PCR positive. 34 out of 39 (87.1%) were <6-18 year old while 5 out of 39 (12.9%) were >3-6 years old. No case was reported in age group 1 month-3 years. Twenty eight patients out of 67 (41.8%) were PCR negative. 17/28 (60.7%) were <6-18 years old. 5 out of 28 (17.9%) were >3-6 years old. 6 out of 28 (21.4%) were 1 month -3 years old. Female: male ratio in PCR positive patients was 1.05:1 while it was 1.54:1 in PCR negative patients. Most of the children came from urban area in both PCR positive and negative results. Cough and fever had a higher frequency in both PCR positive and negative patients while headache was more in epidemic influenza. All PCR positive and 26 out of 28 (92.8%) of PCR negative patients improved while 2 out of 28 (7.2%) of PCR negative patients died. Conclusions: Children at school age were more prone to acquire epidemic influenza. Both genders were equally affected. Frequency was more in urban area .Cough and fever was the most frequent presentation. Headache was a more common presentation in H1N1 influenza than in seasonal influenza.